ANALYSIS OF LEARNING TOOLS DUDIKA INTEGRATED ON MACHINING TECHNIQUE SKILL COMPETENCE - Haris Abizar; Sulaeman Deni Ramdani; Ananda Yhuto Wibisono Putra (Jurnal Pendidikan Teknik Mesin, 2023)
This research aims to analyze the need for DUDIKA-integrated learning tools that can prepare competent graduates. The type of research carried out was descriptive research with a sample of vocational school teachers in the machining engineering and manufacturing industry. Data collection techniques were carried out using interviews, observation, and literature study. The data obtained was analyzed using a qualitative approach. The research results show that the need for DUDIKA's integrated learning tools was obtained through planning by compiling instruments and literature reviews from various relevant journals, collecting data by conducting interviews with teachers and industry as well as learning observation data in schools, and designing learning tools in the form of learning modules. This tool contains theoretical and practical learning by including activities based on the world of work for students. So, this device is an effort to answer challenges for vocational school graduates.